Lumetron Photoelectric Colorimeter Model 400-A - Science History Institute (2018)
Electric-powered meter with instructions housed in wooden box. Movable components within box: two (2) slide glass filters (1 with red, green, and blue slides; 1 with orange, green, and blue slides); one (1) encasing to hold samples.
Keywords: Colorimetry--Instruments; Photovolt Corporation